Contemporary decongestion strategies in acute heart failure: an individual patient data analysis of three randomized controlled trials - Lara E E C Zonneveld; Pieter Martens; Juan C Trullàs; Kevin Damman; Frederik H Verbrugge; Jeroen Dauw; Iris E Beldhuis; Jesús Casado; Jose Luís Morales-Rull; Wilfried Mullens; Jozine M ter Maaten (European Journal of Heart Failure, 2026)
Abstract Aims Recent randomized controlled trials (RCTs) showed improved decongestive response with intensified treatment during hospitalization for acute decompensated heart failure (ADHF). Nevertheless, none demonstrated long-term benefit, possibly due to lack of statistical power. We therefore pooled individual data from three recent RCTs to assess the clinical impact of intensified decongestive therapy. Methods Individual patient data from three RCTs evaluating decongestive strategies in ADHF—acetazolamide (ADVOR), hydrochlorothiazide (CLOROTIC), and natriuresis-guided therapy (PUSH-AHF)—were pooled. The primary endpoint was 90-day heart failure (HF) re-hospitalization and/or all-cause mortality (adjusted for sex and trial). Secondary endpoints included 24- and 48-h diuresis, natriuresis, in-hospital mortality, and length of stay (LOS). Results A total of 1059 patients (mean age 79, 42% female) hospitalized for ADHF were included. Baseline characteristics were similar, except for a higher proportion of men in the intensified treatment arm (63% vs 54%, P = .004). Intensified treatment did not reduce 90-day all-cause mortality and/or HF readmissions (adjusted hazard ratio [HR] 1.03; 95% confidence interval [CI] 0.81–1.30); however, it was associated with lower in-hospital mortality (adjusted odds ratio [OR] 0.55; 95% CI 0.31–0.96; P = .038). Cumulative diuresis and natriuresis was significantly higher in patients with intensified treatment at 24 and 48 h (adjusted P < .001). There was no difference in doubling of serum creatinine at 3 days between the groups (adjusted P = .123). LOS was significantly shorter in patients in the intensified treatment arm (geometric mean of 9 [95% CI 8–9] days vs 10 [95% CI 9–10] days in the placebo group, adjusted P = .002). Conclusion While intensified decongestive strategies in patients hospitalized for ADHF improve diuresis, natriuresis, and reduce LOS, no benefit was observed for post-discharge clinical outcomes. Although a potential reduction in in-hospital mortality was observed, this finding should be considered exploratory and hypothesis-generating.